Greening e-commerce: how e-commerce can promote environmental responsibility - Zolotareva, O.; Yang, Tiantian (Экономика и банки, 2024)
The study is devoted to the progressive development of environmentally friendly electronic commerce, emphasizes the growing importance of environmental stability in the online rendil and the changing perception by consumers of social and environmental responsibility, including the contribution of generation Z to the development of green electronic commerce.